An Evaluation of Industrial Facilities Defects in Selected Industrial Estates in Lagos State, Nigeria - Oseghale, G.E.; Ikpo, I.J. (Institute of Research and Community Outreach - Petra Christian University, 2014)
The study appraised the state of industrial facilities in selected industrial estates established between 1957 and 1981 in Lagos State by examining the nature and causes of facilities’ defects in the selected industrial estates. The buildings sampled were load bearing sandcrete block wall (1%), concrete framed structure (83%) and steel framed structure (16%). Data were sourced using structured questionnaire administered on the staff of maintenance department of 35 building materials and plastic manufacturing industries purposively selected and located in 18 industrial estates. Data obtained were analyzed using descriptive statistic. The study found the structural elements of the buildings, i.e. foundations, beams, walls, and floors satisfactory. Using the mean response analysis, the result showed that the most severe factors responsible for industrial facilities’ defects were combined effects of geo-climatic factors (2.35), combined effects of biological agencies (2.15), corrosion (1.98), and physical aggression on the facilities (1.71).